2023
DOI: 10.1111/dmcn.15578
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of tic severity in children with Tourette syndrome: Motor cortex inhibition measured with transcranial magnetic stimulation

Abstract: AimTo compare transcranial magnetic stimulation (TMS)‐derived measures of primary motor cortex (M1) physiology between children with and without Tourette syndrome, and to dimensionally analyze TMS measures with Tourette syndrome‐related symptom severity.MethodWe used a cross‐sectional experimental design. Sixty 8‐ to 12‐year‐old children participated (30 with Tourette syndrome: three females, mean age 10 years 10 months, standard deviation [SD] 1 year 3 months; 30 typically developing children: seven females, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Several small‐scale studies in adults and adolescents have reported a reduction in SICI; 3 however, this has been less well explored in younger children. Batschelett et al 4 collected several TMS measures (including SICI) from a sample of 30 Tourette syndrome and 30 control participants aged 8 to 12 years. Interestingly, after accounting for ADHD – 15 of the 30 with Tourette syndrome also had ADHD – SICI was not found to be significantly reduced in comparison to controls.…”
mentioning
confidence: 99%
“…Several small‐scale studies in adults and adolescents have reported a reduction in SICI; 3 however, this has been less well explored in younger children. Batschelett et al 4 collected several TMS measures (including SICI) from a sample of 30 Tourette syndrome and 30 control participants aged 8 to 12 years. Interestingly, after accounting for ADHD – 15 of the 30 with Tourette syndrome also had ADHD – SICI was not found to be significantly reduced in comparison to controls.…”
mentioning
confidence: 99%